2013
DOI: 10.1111/ctr.12082
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and albuminuria as predictors of long‐term allograft outcomes in kidney transplant recipients

Abstract: Although cystatin C (Cys) and albuminuria (Alb) are predictors of end-stage renal disease in the general population, there are limited data about the performance of these markers alone or combined with respect to the prediction of the kidney transplant outcome. We assessed the ability of one-yr creatinine (Cr), MDRD equation, Cys, Hoek equation, Alb, the logarithm of albuminuria (LogAlb), and two products of these variables for predicting death-censored graft loss (DCGL) in 127 kidney transplant recipients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Overall our findings are consistent with results for cystatin C and B2M observed in nontransplant populations (14)(15)(16)(17)(18)(19)(20)(21) and extend the current literature of the strong risk factor associations of these filtration markers with important outcomes into the kidney transplant population. Few studies have evaluated risk associated with cystatin C and B2M in kidney transplant recipients (22)(23)(24)(25). In small studies (sample size from 79 to 129) higher cystatin C levels were associated with graft loss (24,25) and higher serum B2M levels were also associated with eGFR cr decline at 1 and 2 years follow-up (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall our findings are consistent with results for cystatin C and B2M observed in nontransplant populations (14)(15)(16)(17)(18)(19)(20)(21) and extend the current literature of the strong risk factor associations of these filtration markers with important outcomes into the kidney transplant population. Few studies have evaluated risk associated with cystatin C and B2M in kidney transplant recipients (22)(23)(24)(25). In small studies (sample size from 79 to 129) higher cystatin C levels were associated with graft loss (24,25) and higher serum B2M levels were also associated with eGFR cr decline at 1 and 2 years follow-up (22).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated risk associated with cystatin C and B2M in kidney transplant recipients (22)(23)(24)(25). In small studies (sample size from 79 to 129) higher cystatin C levels were associated with graft loss (24,25) and higher serum B2M levels were also associated with eGFR cr decline at 1 and 2 years follow-up (22). In the largest study to date, Astor and colleagues reported that higher serum B2M levels at discharge were associated with both mortality and graft loss and with associations of greater magnitude when compared to serum creatinine in a cohort of 2190 primary kidney transplant recipients from a single center in the United States (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical score constructed from a cross-validated French database of 2169 kidney transplant recipients, combining risk factors of graft loss, including SCr and proteinuria, demonstrated to be highly predictive of long-term kidney graft survival [90] , and other study demonstrated that the combination of low-grade albuminuria and decreased eGFR was related with graft loss and mortality [91] . In a similar way, a recent small-sample singlecenter study [92] founded that predictors combining albuminuria and Cr-or CyC-based eGFR, performed better than those markers alone, to predict death censored graft loss, in kidney transplant recipients. Moreover, the best predictor of graft failure in this work was a product of CyC and the logarithm of albuminuria, and CyC-based predictors performed better than Crbased predictors.…”
Section: Creatinine-based and Cyc-based Egfr Equations As Predictors mentioning
confidence: 91%
“…CysC predicts graft survival. However, its superiority over SCr has not been consistently established for this purpose [93,94]. For GFR estimation using the reference standard of mGFR, authors have applied equations ( Supplementary Materials Table S1) that were derived from both non-transplant patients (CKD-EPI, MDRD) and transplant recipients (Rule [90] or Le Bricon [95] equation).…”
Section: Kidney Transplantmentioning
confidence: 99%